Responsibility Land Office of Semarang City In Terms Contained In Land Multiple Certificates - Nur Ismi Hanifah; Umar Ma’ruf (Jurnal Akta, 2019)
Land as one of the natural resources that have a close relationship with human survival. Due to the imbalance between land supply in our country as a result of rapid population growth and increasing development, it can lead to various land disputes including multiple certificates. The purpose of this study to determine the cause of the double land certificate in Semarang and Semarang Land Office responsibilities in the event of multiple land certificates as well as the barriers and solutions Land Office responsibilities in the completion of the double land certificate in Semarang.The method used in this research is the method of juridical-sociological. Specifications are descriptive analytical research. The data used primary data and secondary data obtained by interview and literature study. Qualitative data analysis, the problem was analyzed by the theory of the legal system, legal certainty and legal responsibilities.The results showed that the cause of the land multiple certificates in the Land Office of Semarang is the first that structure, that possible errors and omissions of agencies, both which are substances that can be made possible on the legislation governing the registration of land and the third is Culture Law, uncaused of view of the society on land certificates. The responsibility of the Land Office of Semarang in It contained a land multiple certificates is the Regulation of the Minister of ATR / BPN No. 11 of 2016 on the Settlement of Cases of Land, which is after all the research is done, the land office is obliged to cancel one of them if there were procedural errors in the case of defective administration and conditions other rule. Obstacles Land Office in the completion of a land multiple certificates in Semarang is external (the parties are not present and not good faith when mediation) and internal (Land Office only as a mediator is not a court), so the solution in order to give rise to legal certainty then the settlement of disputes through State court and State Administrative court.Keywords: Responsibility; Land; Associate Certificate.